2013
DOI: 10.1111/hae.12315
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in health‐related quality of life with recombinant factor IX prophylaxis in severe or moderately severe haemophilia B patients: results from the BAX326 Pivotal Study

Abstract: Little is known about the health-related quality of life (HRQoL) burden of haemophilia B. The aim of this study was to assess HRQoL burden of haemophilia B, the benefit of recombinant factor IX (rFIX) prophylaxis and the HRQoL benefit of achieving a zero annual bleed rate. Subjects receiving rFIX (BAX326) prophylaxis or on-demand completed the SF-36 survey. Baseline SF-36 scores were compared to the general US population scores to understand the HRQoL burden. Changes in SF-36 scores between baseline and follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 18 publications
(28 reference statements)
3
38
0
Order By: Relevance
“…The study confirmed the PK equivalence of the 2 products based on area under the curve (AUC) of plasma concentration versus time from 0 to 72 hours (AUC 0-72h ) [Windyga et al 2014a]. Repeated PK analysis at the end of the 6-month study in the third part of the study confirmed the initial findings for BAX326.…”
Section: Pivotal Phase I/iii Studysupporting
confidence: 68%
See 4 more Smart Citations
“…The study confirmed the PK equivalence of the 2 products based on area under the curve (AUC) of plasma concentration versus time from 0 to 72 hours (AUC 0-72h ) [Windyga et al 2014a]. Repeated PK analysis at the end of the 6-month study in the third part of the study confirmed the initial findings for BAX326.…”
Section: Pivotal Phase I/iii Studysupporting
confidence: 68%
“…The overall median annualized bleeding rate (ABR) during the 6 months of twice-weekly prophylaxis with BAX326 was 1.99 (range 0-23.4). The overall mean ABR (4.20 ± 5.75) was significantly lower (79% difference; p < 0.001) than that seen in a historic control group of 276 patients who had received on-demand treatment (rFIX or pdFIX) in 12 earlier studies (20.0 ± 39.4) [Windyga et al 2014a]. Of 249 reported bleeds in the pivotal study, 211 (84.7%) were controlled with 1-2 infusions.…”
Section: Pivotal Phase I/iii Studymentioning
confidence: 80%
See 3 more Smart Citations